Construction of a g-C3N4-driven photocatalytic system for boosted biomass-derived alcohol oxidation: a promising route towards sustainable biomass valorization. Issue 4 (31st January 2023) - Cui, Jifang; Lu, Xuebin; Guo, Mengyan; Zhang, Ming; Sun, Linhao; Xiong, Jian; Zhang, Rui; Li, Xiaoyun; Qiao, Yina; Li, Dan; Guo, Mingyu; Yu, Zhihao
Abstract : We present feasible regulation strategies of a g-C3 N4 -based photocatalytic system for selective oxidation of biomass-derived alcohols for better biomass valorization. Abstract : As one of those natural carbon-based non-toxic and non-metallic materials, g-C3 N4 has exhibited excellent electronic and structural properties that make it versatile as an efficient photocatalyst, which was widely mentioned in applications of photocatalytic oxidation reactions. Recently, a gradually increased number of research efforts have been focused on the development of novel g-C3 N4 -based composite catalysts for better photocatalytic biomass valorization. In this context, this paper aims to retrospect the progress of the g-C3 N4 -driven photocatalytic oxidation of biomass-derived alcohols represented by 5-hydroxymethylfurfural (HMF) and benzyl alcohol (BA). The core concerns are discussed to elaborate the effects of structural regulating approaches of g-C3 N4 -based photocatalysts on biomass-derived alcohol oxidation performance, involving intrinsic structure optimization, dye sensitization, and heterojunction construction. Also, influences of key external condition parameters, including the light source, oxygen source, and solvent, on the g-C3 N4 -based photocatalytic system are discussed. The viewpoints proposed in this paper may contribute to the design, synthesis, and modification of novel g-C3 N4 -based photocatalytic materials, thus providing potential opportunities to enhance the photocatalytic selective oxidation performance of biomass-derived alcohols for a better sustainable biomass refining system.